Baruch Spinoza - De Biasi, Elettra (Philosophy Kitchen - Rivista di filosofia contemporanea, 2024)
Baruch Spinoza, one of the most influential philosophers of the 17th century, still occupies a central place in modern and contemporary philosophy due to his unitary view of reality and his profound impact on various fields of thought. Spinoza presents a reality that must be justified in its unitary totality, a place where the absolute is realised and unfolds continuously. Spinoza urges us to understand that truth is not an autonomous and complete reality, but rather that only the partial is real, if it is not to become an empty metaphysical concept.